An evaluation of the City of Armadale's incentive for higher density development through Town Planning Scheme No. 4 in the context of sustainability - Luscombe, Simon David (Curtin University, 2008)
The densification of established urban areas has become a key strategy in an attempt to accommodate increases in urban populations. Through a case study investigation within the City of Armadale, the perceived costs and benefits of increasing residential densities are evaluated with reference to stakeholder opinion as well as social, environmental and economic performance. This study sets out to evaluate the impact of the recently gazetted City of Armadale Town Planning Scheme No. 4. The City of Armadale is situated on the outskirts or ‘mortgage belt’ of Perth, and has not previously been subject to higher zonings than R15. Higher residential densities are thus relatively new to Armadale where the potential for expansion has effectively increased by almost 50% under the scheme by a newly introduced dual coding mechanism. The potential to increase residential zonings and build additional dwellings on single lots has introduced a number of issues not anticipated by Council including grouped housing developments ‘not meeting the standards expected’ (City of Armadale 2007). This has resulted in Council’s desire for additional guidance and regulation in an attempt to improve standards. The intention of this research is to assess the extent to which the Residential Design Codes and local planning schemes produce positive planning outcomes, as well as determining the effectiveness of the role of local planning policies in guiding development.Findings of research undertaken indicate that Council views its role as regulator in a system prone to exploitation. Increased zonings do not necessarily result in a widespread loss of vegetation, nor an increase in land values. Social factors are significant in planning, accommodated within local planning schemes and local planning policies. Many planners believe a balance between urban infill and sprawl is necessary and the Residential Design Codes in isolation are insufficient to ensure a high standard of development, with the majority surveyed favouring a regulated approach. A number of research tools have been utilised in determining the impacts of revising a local planning scheme and policies including observational studies, document analysis, surveys and interviews. In conclusion, this thesis makes recommendations to improve the form and design of medium density residential developments in Armadale from the perspectives of the market's producers and consumers.